94. Chronic pure motor axonal plexopathy responsive to immunomodulatory treatment: Clinical, electrophysiological and magnetic resonance imaging correlations. Issue 1 (January 2015) - Donato, F.; Morini, A.; Zimatore, S.; Romito, S.; Alessandrini, L.; Moretto, G.; Squintani, G.
<x xml:space="preserve">Abstract</x> A 70 year old woman with a diagnosis of left radial nerve entrapment at the arcade of Frohse, unsuccessfully surgically treated, came to our attention for a progressive weakness in her left arm that began 6 years before. Neurological examination showed severe hypotrophic muscles innervated by left ulnar and radial nerves and reduced strength at the level of forearm flexors, arm and shoulder muscles. No sensory deficits were reported. Serum antiganglioside antibody research and cerebrospinal fluid analysis was negative. EMG testing revealed neurogenic MUPs and poor recruitment in left forearm, arm and shoulder muscles and low cMAP amplitude stimulating the left radial and ulnar nerve associated to active denervation. No sensory impairment or conduction blocks detected with proximal stimulation and collision techniques were present. MRI disclosed hyperintensity on T2-weighted STIR sequences of the left brachial plexus, compatible with hypertrophic neuropathy. The patient was treated with ivIg with clinical benefit. The MRI and electrophysiological picture in our patient, together with response to ivIg, were consistent with a diffuse inflammatory process affecting the brachial plexus, with very likely axonal pathophysiology. Disimmune axonopathies should be recognised because are treatable disorders: MRI in selected cases, may be considered in the diagnostic work-up of disimmune neuropathy/plexopathy.